Hyper-Local Marketing Strategy in Communicating the Benefits of Local Community Products - Iing Saefudin (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2025)
This research aims to analyze the implementation of hyper-local marketing strategies carried out by local communities in communicating the advantages and added value of their products. In the midst of increasingly massive market competition, marketing approaches based on specific geographic areas are considered capable of building emotional closeness with local consumers. Using qualitative descriptive methods, data collection was carried out through observation, in-depth interviews with community administrators, and analysis of the use of location-based digital platforms. The research results show that optimizing hyper-local marketing does not depend on financial capital or complicated technological algorithms, but rather relies on the synergy of three main pillars which include spatial digital accessibility, narrative authenticity of local wisdom through storytelling techniques, and strengthening communal social ties through instant messaging applications for residents and local events. Limiting the target market to a micro geographic radius has proven effective in triggering an exponential word-of-mouth marketing effect and building regional economic resilience from the grassroots level. This research concludes that strengthening social capital-based connections between local communities and the surrounding community is the key to the success of the micro-scale marketing model.